ANALISIS LAJU PENDINGINAN BAHAN MAKANAN DALAM COOLBOX UNTUK PEMASARAN DENGAN WATER MISTING SYSTEM DI KOTA AMBON - Leslie S Loppies; Eka Rahmat Mahayani Anthonio Putera Lilipaly (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2021)
Food preservation can be done by using cooling system, however, the preservation used in Ambon traditional market is still the old ways of pouring cold water on the materials. The method caused many types of pollution such as smell, dirty puddle, and the damage of the road. By using a more effective and efficient cooling system, the food material is expected to be more clean, the market will be better and less damaged road. This will result in a happier customer and seller. The water misting system can keep the materials temperature at 10-15⁰C. The materials use is kale and fish. These materials can last all day and looked fresh. This system did not create pollution, dirty water puddle, and also consumed less water.